Implementation of research evidence in orthopaedics: a tale of three trials. Issue 5 (27th November 2019) - Reeves, Katharine; Chan, Samuel; Marsh, Alastair; Gallier, Suzy; Wigley, Catrin; Khunti, Kamlesh; Lilford, Richard J
Abstract : Objective: To examine implementation of evidence in orthopaedic practice following publication of the results of three pivotal clinical trials. Design: Case studies based on three orthopaedic trials funded in sequence by the National Institute for Health Research Health Technology Assessment (HTA) programme. These trials dealt with treatment of fractures of the humerus, radius and ankle, respectively. For each case study, we conducted time-series analyses to examine the relationship between publication of findings and the implementation (or not) of the findings. Results: The results of all three trials favoured the less expensive and less invasive option. In two cases, a change of practice, in line with the evidence that eventually emerged, preceded publication. Furthermore, the upturn in use of the intervention most supported by each of these two trials corresponded to the start of recruitment to the respective trial. The remaining trial failed to influence practice despite yielding clear-cut evidence. Conclusions: Implementation of results of all three HTA orthopaedic trials favoured the less expensive and less invasive option. In two of the three studies, a change in practice, in line with the evidence that eventually emerged, preceded publication of that evidence. A trend or a change in practice, at around the start of the trial, indicates that the direction of causation opposes our hypothesis that publication of trial findings would lead to changes in practice. Our results provide provocative insight into the nuanced topic of research and practice, but further qualitative work is needed to fully explain what led to the pre-emptive change in practice we observed and why there was no change in the third case.